100 years of immunotherapy: the Monaco charter - Canonica, Giorgio Walter; Baena Cagnani, Carlos E.; Compalati, Enrico; Bohle, Barbara; Bonini, Sergio; Bousquet, Jean J.; Cox, Linda; Fink Wagner, Antje H.; González Díaz, Sandra Nora; Jacobsen, Lars; Passalacqua, Giovanni; Pawankar, Ruby; et al. (S. Karger Medical and Scientific Publishers, 2012)
Aims of the Monaco Charter: (1) to present the current evidence on the efficacy and safety of allergen-specific immunotherapy (SIT) and to address the reasons for its underuse in clinical practice; (2) to develop strategies to increase the awareness about the benefits and the hazards of SIT in allergic patients, lay public and healthcare professionals not trained in allergy, and (3) to make SIT accessible and affordable to eligible patients.